Karakteristik Semen Segar dan Kualitas Semen Cair Kuda dalam Pengencer Dimitropoulos yang Disuplementasi dengan Fruktosa, Trehalosa dan Rafinosa - . Yudi; I Arifiantini; B Purwantara; T L Yusuf (Faculty of Animal Science, Bogor Agricultural University, 2007)
The objective of the experiment was to study the characteristics of stallion fresh semen and the quality of sperm preserved in Dimitropoulos extender (DV) supplemented with different concentration of fructose, trehalose and raffinose. Semen were collected using artificial vagina from three stallions. Semen characteristics and quality were evaluated macro- and microscopically. Prior to extension, semen were centrifugated at 3000 rpm for 20 minutes. The condensed sperm were re-suspended in DV supplemented with different types of carbohydrate to meet the concentration of 200 million spz/ml. All samples were stored at room and chilled temperature, and were evaluated for motility and viability every 3 h and 12 h. The results of the experiments indicated that fresh semen characteristics were fair good; the volume, consistency, motility, live-dead ratio, concentration (106/ml), total spermatozoa (109/ejaculate) and abnormality were 29.25±9.33 ml, watery, 7.00±0.12, 67.08±9.08%, 77.89±6.46%, 211.88±21.15, 6.28±2.45 and 27.26±4.64%, respectively. The supplementation of different type and concentration of carbohydrates did not significantly affect the motility and viability. However, the supplementation of 50 mM fructose significantly increased the motility and viability of the sperm compared to the control. In conclusion, carbohydrate supplementation in DV may not maintain the sperm quality, particularly in the medium with the osmolarity higher than 400 mOsm/kg. Key words: stallion, semen, Dimitropoulos, carbohydrate